Metastatic osteogenic sarcoma or multifocal osteosarcoma: A case report - Dahal, Sunit; Rajak, Asish; Rajak, Ashik (Journal of Kathmandu Medical College, 2021)
Multifocal osteosarcoma is a rare condition in which multiple osteogenic sarcoma at various regions are present at diagnosis. These account for 1-3 percent of all osteogenic sarcoma. A thirteen-year-old female presented with pain and swelling over her right thigh for a duration of three months with no history of trauma. The diagnosis of osteosarcoma was suspected through radiology which incidentally also showed the other femur to have involvement while getting the MRI scan. A suspicion of either metastatic osteogenic sarcoma or multifocal osteosarcoma was made and CT of the chest was done to look for pulmonary metastasis. The diagnosis was confirmed by biopsy from the right thigh. The diagnosis was confirmed as metastatic osteogenic sarcoma. There is always suspicion whether these tumors represent osseous metastasis or are of multicentric origin. This case is of interest because there was high suspicion that it could be multifocal osteosarcoma which would have been a very rare case.